Ekologistyka w gospodarce odpadami w obszarze miasta i regionu - Kaźmierski, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Logistics - as a modem koncept of management - manages the flow of goods, service and information in order to improve the effectiveness, which gains popularity in every area of management. In this study, the author presents particular applications of logistics, namely, the conservation management, with the emphasis on the problem of ecologistics applied to the refuse economy in cities as well as larger areas.The author describes the aims as well as potential benefits which can be achieved through the application of ecologistics to the refuse economy.The study includes the comparisons between Polish refuse economy and foreign models. What is more, it reveals certain requirements connected with this issue and Polish accession to the European Union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 664-672